Pharmacological Activity, Pharmacokinetics, and Toxicity of Timosaponin AIII, a Natural Product Isolated From Anemarrhena asphodeloides Bunge: A Review - Lin, Yan; Zhao, Wai-Rong; Shi, Wen-Ting; Zhang, Jing; Zhang, Kai-Yu; Ding, Qian; Chen, Xin-Lin; Tang, Jing-Yi; Zhou, Zhong-Yan (Frontiers in Pharmacology, 2020)
Anemarrhena asphodeloides Bunge is a famous Chinese Materia Medica and has been used in traditional Chinese medicine for more than two thousand years. Steroidal saponins are important active components isolated from A. asphodeloides Bunge. Among which, the accumulation of numerous experimental studies involved in Timosaponin AIII (Timo AIII) draws our attention in the recent decades. In this review, we searched all the scientific literatures using the key word “timosaponin AIII” in the PubMed database update to March 2020. We comprehensively summarized the pharmacological activity, pharmacokinetics, and toxicity of Timo AIII. We found that Timo AIII presents multiple-pharmacological activities, such as anti-cancer, anti-neuronal disorders, anti-inflammation, anti-coagulant, and so on. And the anti-cancer effect of Timo AIII in various cancers, especially hepatocellular cancer and breast cancer, is supposed as its most potential activity. The anti-inflammatory activity of Timo AIII is also beneficial to many diseases. Moreover, VEGFR, X-linked inhibitor of apoptosis protein (XIAP), B-cell-specific Moloney murine leukemia virus integration site 1 (BMI1), thromboxane (Tx) A2 receptor, mTOR, NF-κB, COX-2, MMPs, acetylcholinesterase (AChE), and so on are identified as the crucial pharmacological targets of Timo AIII. Furthermore, the hepatotoxicity of Timo AIII was most concerned, and the pharmacokinetics and toxicity of Timo AIII need further studies in diverse animal models. In conclusion, Timo AIII is potent as a compound or leading compound for further drug development while still needs in-depth studies.